Pathogenesis of chronic rhinosinusitis in patients affected by β-thalassemia major and sickle cell anaemia post allogenic bone marrow transplant. (March 2018) - Martino, F.; Di Mauro, R.; Paciaroni, K.; Gaziev, J.; Alfieri, C.; Greco, L.; Floris, R.; Di Girolamo, S.; Di Girolamo, M.
Abstract: Objectives: Sickle cell anemia (SCA) and β -thalassemia major are well-recognized beta-globin gene disorders of red blood cells associated to mortality and morbidity included bone morbidities due to ineffective erythropoiesis and bone marrow expansion, which affect every part of the skeleton. While there are an abundance of described disease manifestations of the head and neck, the manner of paranasal sinuses involvement and its relations to β-thalassemia and SCA process was not studied yet. Therefore, the aim of this study was to investigate a possible increased risk of rhinosinusitis and the real pathogenetic mechanism of it, comparing these two hematological diseases using msCT, gold standard for paranasal sinuses evaluation. Methods: A retrospective analysis of 90 patients affected by β-thalassemia major or SCA (respectively 59 and 31) underwent allogeneic bone marrow transplantation (BMT), and 44 control subjects was performed. Both patient categories and control group have been subjected to hematological and radiological evaluation using 64-multidetector-row CT scanner without contrast injection. Results: Statistical analysis reveals that patients of the two study groups exhibit a significantly increased risk of sinusitis in comparison with the normal controls (RR: 3.55 for β-thalassemic pediatric subjects; RR: 3.35 for SCA pediatric subjects). A significant difference (p < 0, 5) was found between the β -thalassemic patients on the one side, and SCA and control group on the other side, with regard to the evaluation of the typical anatomic alteration of maxillary sinus: β-thalassemic children had significant increase in the bone thickness of anterior and lateral sinus walls and significant reduction in volume and density compared to SCA patients and control group, with normal conditions of these parameters. Conclusions: In these hematological patients, there is an increased incidence of sinonasal infections due their therapy-induced immunosuppression post transplantation. In β-thalassemic patients, furthermore, the specific anatomical variants play an important confounding factor in radiological interpretation of CT images. Therefore, a cranio-facial CT scan evaluation could be a useful tool in the management of upper airway infections after BMT and should be a routinely exams in order to avoid useless surgical or antibiotic approaches.